China English: its ideological nature and implications for translation and interpreting. (2nd October 2017) - Chang, Pin-Ling
ABSTRACT: China English, a term coined in 1980, is now widely recognised both inside and outside China as a developing variety of English loaded with characteristics of the Chinese culture and language. Using China English rather than the international variety enables the Chinese general public to retain their national and cultural identity and Chinese interpreters and translators to safeguard the national interest and dignity. For some, it is also a way of breaking the hegemony of English as a global language while establishing itself as a hegemonic discourse in its place. By discussing its development, theoretical foundations and application in the training and practice of translation and interpreting, this paper aims to uncover the ideological nature and implications of China English for the world.